The Relationship of Individual and Occupational Factors with Complaints of Tendinitis in Transport Workers at Bulog Talumolo Rice Warehouse Bulog Bulog Gorontalo Branch Office - Irma Azzahra Usman; Laksmyn Kadir; Putri Ayuningtias Mahdang (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Transportation workers in rice warehouses have a high risk of experiencing unergonomic work postures, excessive physical workload, and high lifting frequencies that can trigger tendinitis complaints. These complaints can be influenced by various factors, both individual factors and work factors. This study aims to determine the relationship between individual factors and occupational factors with tendinitis complaints in transport workers at Bulog Talumolo Rice Warehouse, Gorontalo. This study uses a quantitative research methodology with observational analytical research types and cross-sectional design. The population and sample in this study amounted to 50 transport workers, the sampling technique was a total sampling. The statistical test used in this study is the Spearman Rank test. The results of the analysis using the Spearman Rank test showed that there was a significant relationship between individual factors, namely age (p = 0.000; r = -0.594), body mass index (p = 0.002; r = 0.424), and occupational factors, namely work posture (p = 0.032; r = 0.304), physical workload (p = 0.019; r = 0.331), and tendinitis complaints. The conclusion that individual and occupational factors are significantly related to tendinitis complaints. It is recommended that there be ergonomic interventions, training on correct working postures, and reduction of repetitive workload as an effort to prevent tendinitis complaints in transport workers.